The Socio-economic Conditions of Fishers on Indonesia's Beeng Laut Island - Costantein Imanuel Sarapil; Eunike Irene Kumaseh; Getruida Nita Mozes (Faculty of Geography, Universitas Gadjah Mada, 2022)
This study aimed to determine the socio-economic conditions related to marketing margins of demersal fish in Beeng Laut Island, Sangihe Archipelago Regency, North Sulawesi Province, Indonesia, using survey methods with interview and questionnaire techniques. Most fishers on Beeng Laut Island have a primary school education, houses constructed using wood, and an age range of 20 to 30 years. Margin marketing demersal fish on Channel marketing III (P à Pp à Pe à Ka) and Channel IV (P à Pp à Rm à Ka) is inefficient due to the limited electricity supply. This has an indirect effect on fish quality due to a lack of readily available ice to handle catches. Increased demersal fish marketing efficiency may result in a significant revenue for fishers. Therefore, the government should boost energy availability to enable people create and purchase ice to aid with fish preservation. It should also establish cooperatives for fishers and provide alternative work, such as conservation activities or marine tourism development.